STUDY ON MECHANICAL PROPERTIES OF POROUS SCAFFOLD AND DESIGNING OF MANDIBULAR PROSTHESIS BASED ON SLM FORMING - YAN HanSheng; WEI Bo; LIU Chris; QIU YongLiang (Jixie qiangdu)
The tissue engineered bone provides an important method for repairing large segmental bone defects.However,how to design a prosthesis that matches the mechanical properties of host bone remains to be studied.Therefore,this study aimed to explore the scaffold mechanical properties based on selective laser melting(SLM)fonning printing technology for scaffold and apply to mandibular reconstruction.Firstly,hexahedral(HE),octahedral(OC)and body centred cubic(BCC)unit cell porous scaffolds with different porosity(50%-80%)were established,and the porous scaffold mechanical properties were analyzed by finite element analysis.Secondly,the porous Ti6Al4V scaffolds with strong mechanical properties were prepared by SLM forming technology,and the scaffold mechanical properties were evaluated by the compression test.Finally,the least square method was used to fit the scaffold porosity⁃elastic modulus curve,so as to obtain the porous prosthesis with mechanical properties matching the mandibular defect region.The results show that the maximum stress of porous scaffold increases with the increase of porosity and is closely related to the configuration(BCC>OC>HE).The compression test shows that the scaffold elastic modulus with different porosities is significantly different,and the porosity is inversely proportional to the elastic modulus.According to the Gibson⁃Ashby model of hexahedral unit cell scaffold,the ideal prosthesis porosity is 53.1%.Additionally,the safety of the prosthesis is verified by finite element analysis.The finite element analysis and compression test confirmed that the scaffold mechanical properties with different porosities are discrepant,and the optimized prosthesis with appropriate porosity can better match the mechanical properties of host bone,which provides valuable insights for implant design.